D4 is the measles virus which caused the measles outbreak in 2004 in Iraq - Alizi, Sana'a Muhammad Hussain; Alhaidari, Raghad Ali (Journal of the Faculty of Medicine Baghdad, 2008)
Background: no previous study is done in Iraq about the isolation and the identification of measles virus although the outbreaks were continuous in the previousyears.Aim of the study: To identify our local strain of measles virus, which had caused measles o utbreak in the year 2004.Patient and methods: About (55) Urine samples and (80) throat swabs were collected from 88 measles suspected patients all over the country during measlesoutbreak of the year 2004. Serological (ELISA) and virological test were used for this purpose.Results: Measles virus was isolated successfully in 16 patients who had symptoms of measles infection from mid and south of Iraq. These isolates were obtained on B95aand Vero Slam cell line in 2004. Measles isolates was identified in WHO RRL as D4 genotype.Conclusion: The study shows that Vero Slam is batter than B95a for measles isolation and this is the first attempt to get measles isolates on B95a cell line incomparison with using Vero Slam cell line. In addition to that it was the first study had identified the endemic strain of measles virus (D4) in Iraq.